Populisme Mahkamah Konstitusi dalam Penafsiran Perkara-Perkara pada Wilayah Open Legal Policy - Idul Rishan (Fakultas Hukum Universitas Islam Indonesia, 2024)
In the past seven years, the striking characteristic of cases filed before the Constitutional Court (MK) has developed into cases at the open legal policy level. In open legal cases, policy amendments should be settled through the formation or improvement of laws by the government. This study aims towards three objectives: (1) to identify the causes of the emergence of open legal cases filed before the Constitutional Court (2) to analyse the types of interpretations by the Constitutional Court in regards to open legal cases (3) to assess the level of public satisfaction relating to the decisions in open legal cases. The present research is a mixed legal study that utilises both primary and secondary data. The results of the study indicate that (1) the increasing number of open legal submissions at the Constitutional Court is caused by precedents where the Constitutional Court's interpretation of laws is considered swifter in obtaining legal certainty than encouraging the formation or amendment of laws through the President and the DPR. (2) In open legal cases, the interpretation of the Constitutional Court is highly dynamic. There is not a single type of interpretation, either judicial activism or judicial restraint, that is often used consistently in examining and deciding cases in the open legal area. (3) The results of this study also found that the Constitutional Court has not always been a populist in its decisions on open legal cases. There is even no correlation between interpretive judicial activism and judicial restraint with the level of public satisfaction towards the open legal cases.Keywords: Constitutional Court, Judicial Activism, Judicial Restraint, Open Legal Policy. AbstrakDalam tujuh tahun terakhir, karakteristik perkara yang dimohonkan ke Mahkamah Konstitusi (MK) berkembang pada perkara-perkara pada level kebijakan hukum terbuka (open legal policy). Dalam perkara open legal, perubahan kebijakan seharusnya diselesaikan melalui pembentukan atau perbaikan undang-undang oleh pemerintah. Studi ini bertujuan untuk memperoleh tiga hal, yaitu (1) mengidentifikasi penyebab munculnya perkara-perkara open legal yang dimohonkan di MK, (2) menganalisis jenis penafsiran (MK) dalam perkara open legal, (3) tingkat kepuasan publik terhadap putusan dalam perkara open legal. Studi ini merupakan penelitian hukum campuran (mix legal studies) dengan menggunakan data primer dan data sekunder. Hasil studi menunjukan (1) maraknya permohonan open legal di MK disebabkan oleh preseden dimana penafsiran MK terhadap undang-undang dinilai lebih cepat dalam memperoleh kepastian hukum ketimbang mengusulkan pembentukan atau perubahan undang-undang melalui Presiden dan DPR. (2) Dalam perkara open legal, penafsiran MK sangat dinamis. Tidak ada satu jenis penafsiran baik activism maupun restraint yang kerap digunakan secara konsisten dalam memeriksa dan memutus perkara di wilayah open legal. (3) Hasil studi ini juga menemukan bahwa MK tidak selalu populis dalam putusan-putusan perkara open legal. Bahkan tidak terdapat korelasi antara penafsiran activism maupun restraint dengan tingkat kepuasan publik pada perkara open legal. Kata Kunci: Judicial Activism, Judicial Restraint, Mahkamah Konstitusi, Open Legal Policy.